Dechlorination agent, its preparation method and application
Patent Information
- Application Number
- CN202611305723.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]本发明提供了一种脱氯剂及其制备方法和应用,以解决现有脱氯剂中比表面积利用率低、孔容和孔径分布不合理、机械强度与水热稳定性不足、穿透氯容偏低的问题
1.本发明提供的一种脱氯剂的制备方法,包括如下步骤:S1,将钙源、铝源、铁源、稀土氧化物经共沉淀反应得到混合物料A;S2,将混合物料A、疏水分子筛、扩孔剂混合挤条成型、分段焙烧得到中间体;S3,将分散稳定剂、络合型碱催化剂、有机硅源、有机硼源、醇类溶剂混合,缓慢滴加水,分段熟化,得到硼硅纳米溶胶;所述有机硅源、有机硼源的摩尔比为1:(0.20-0.25);S4,将中间体在硼硅纳米溶胶中浸渍、煅烧,得到所述脱氯剂。
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of purification agent technology, specifically to a dechlorination agent, its preparation method, and its application. Background Technology
[0002] In the petrochemical industry, process gases produced by high-temperature processes such as catalytic reforming, hydrorefining, and hydrocarbon steam reforming typically contain a certain concentration of hydrogen chloride. Chlorine components not only cause corrosion of pipelines and reactors, affecting equipment safety, but also readily react with active components in downstream hydrogenation, reforming, and purification catalysts, leading to irreversible catalyst poisoning and failure. Simultaneously, the ammonium salts formed by the combination of chlorine and ammonia can cause pipeline blockage and scaling. Therefore, installing dechlorination devices in high-temperature process sections and using high-temperature dechlorinating agents to achieve deep dechlorination and purification of process gases is a key technical means to ensure the long-term stable operation of subsequent catalysts. Currently, industrial high-temperature dechlorinating agents generally use metal oxides (such as calcium, magnesium, and zinc) as active components, loaded onto porous supports such as alumina and molecular sieves. Their dechlorination performance and service life directly depend on the synergistic optimization level of core physicochemical parameters such as specific surface area, pore volume, pore size, mechanical strength, and chlorine penetration capacity.
[0003] However, existing high-temperature dechlorination agents still generally suffer from the following technical bottlenecks in practical industrial applications: First, the active component dispersion is poor. Most existing dechlorination agents use physical blending to combine the active component with the carrier, making it difficult to achieve uniform dispersion at the molecular level. The resulting large crystal particles lead to low effective surface area utilization. During long-term high-temperature operation, the unevenly dispersed active component is prone to migration and aggregation, reducing effective active sites and causing the chlorine penetration capacity to be far lower than the theoretical capacity, significantly shortening the dechlorination agent's lifespan. Second, the carrier has a simple pore structure, mainly micropores, lacking a reasonable hierarchical pore structure design. The excessively high proportion of micropores leads to a low total pore volume, and the lack of mesopores / macropores as material transport channels results in high internal diffusion resistance and poor accessibility of active sites. Under sulfur-containing high-temperature atmospheres, sulfides easily deposit at the micropore openings, causing rapid blockage, significant loss of effective pore volume, deterioration of pore size distribution, poor resistance to sulfur poisoning, rapid decay of chlorine penetration capacity, and severely limited applicable operating conditions. Third, alumina-based carriers have strong hydrophilicity and insufficient hydrothermal stability. In high-temperature, water-containing atmospheres, water molecules readily interact with the alumina support, causing the support's crystal lattice structure to collapse, resulting in a significant decrease in specific surface area and pore volume, and consequently a substantial reduction in mechanical strength. While excessive addition of binder can improve strength, it further sacrifices pore volume and pore size, creating a contradiction between strength and pore structure, leading to significant operational risks such as bed collapse and reduced efficiency. Under the combined influence of these factors, the penetration chlorine capacity of the dechlorinating agent rapidly declines under sulfur-containing, water-containing, and high-temperature conditions, making it difficult to meet the industrial requirements for long-term stable operation. Summary of the Invention
[0004] This invention provides a dechlorination agent, its preparation method, and its application to solve the problems of low specific surface area utilization, unreasonable pore volume and pore size distribution, insufficient mechanical strength and hydrothermal stability, and low chlorine penetration capacity in existing dechlorination agents.
[0005] In a first aspect, the present invention provides a method for preparing a dechlorinating agent, comprising the following steps: S1, obtaining a mixture A by co-precipitation reaction of a calcium source, an aluminum source, an iron source, and a rare earth oxide; S2, extruding and calcining a mixture A, a hydrophobic molecular sieve, and a pore-expanding agent to obtain an intermediate; S3, mixing a dispersant stabilizer, a complexing alkali catalyst, an organosilicon source, an organoboron source, and an alcohol solvent, slowly adding water, and aging in stages to obtain a borosilicate nanosol; wherein the molar ratio of the organosilicon source to the organoboron source is 1:(0.20-0.25); S4, impregnating and calcining the intermediate in the borosilicate nanosol to obtain the dechlorinating agent.
[0006] As an example, the molar ratio of the organosilicon source and the organoboron source includes 1:0.20, 1:0.205, 1:0.21, 1:0.215, 1:0.22, 1:0.225, 1:0.23, 1:0.235, 1:0.24, 1:0.245, 1:0.25, or falls within any range of the above values; In an optional embodiment, in step S1, the mass ratio of the calcium source, aluminum source, iron source, and rare earth oxide is 1:(1-2):(0.1-0.1429):(0.005-0.024). In one optional embodiment, in step S2, the mass ratio of the mixture A, the hydrophobic molecular sieve, and the pore-expanding agent is 1:(0.03-0.06):(0.03-0.05). In one optional embodiment, in step S2, the pore-expanding agent includes organic pore-expanding agents and inorganic pore-expanding agents; Optionally, the mass ratio of organic pore expander to inorganic pore expander in the pore expander is 1:1-1.2; In an optional embodiment, in step S3, the molar ratio of the organosilicon source, organoboron source, complexed base catalyst, alcohol solvent, and water is 1:(0.20-0.25):(0.09-0.16):(9-11):(2.2-2.8). In one optional embodiment, in step S3, the amount of dispersant stabilizer added is 1.0%-1.5% based on the mass of the alcohol solvent.
[0007] In one optional embodiment, in step S1, the coprecipitation reaction includes mixing calcium source and water at a mass ratio of 1:(2.0-3.0) to form a calcium source suspension, heating to 45-55°C and adding aluminum source, iron source and rare earth oxide, heating to 75-85°C and stirring for 25-35 minutes, and then separating the solid and liquid to obtain mixture A.
[0008] In one optional embodiment, step S2, the segmented calcination includes drying at 80-120℃ for 2-3 hours, calcining at 280-320℃ for 1.5 hours, and finally calcining at 480-550℃ for 3-4 hours.
[0009] In one optional implementation, in step S3, the dripping time of the water is controlled to be 40-60 minutes; In one optional implementation, step S3 includes segmented ripening at room temperature in a sealed environment for 2.5-3.5 hours, followed by sealed ripening at 30-35°C for 4-6 hours.
[0010] In an optional embodiment, in step S4, the impregnation includes impregnating the intermediate and borosilicate nanosol at a volume ratio of 1:(1-2) at room temperature for 20-30 minutes. And / or, in step S4, the calcination temperature is 480℃-500℃, and the holding time is 3.5-4.5h; And / or, in step S2, the mixing step further includes adding a binder; Optionally, the adhesive includes at least one of water and CMC solution.
[0011] In one optional embodiment, in step S4, the calcination includes heating to 480℃-500℃ at a rate of 1-2℃ / min and holding at that temperature for 3.5-4.5 hours. In one optional embodiment, the rare earth oxide includes at least one of cerium dioxide, lanthanum trioxide, and yttrium trioxide; In one optional embodiment, the calcium source includes at least one of calcium hydroxide and calcium oxide; In one optional embodiment, the aluminum source includes at least one of boehmite, fast-release powder, and activated alumina powder; In one optional embodiment, the iron source includes at least one of iron oxide, iron oxide red, and iron hydroxide. In one optional embodiment, the dispersion stabilizer includes at least one of polyethylene glycol 400 and polyethylene glycol 350; In one optional embodiment, the complexed base catalyst includes at least one of triethanolamine and diethanolamine; In one optional embodiment, the organosilicon source includes at least one of tetraethyl orthosilicate and tetrabutyl orthosilicate; In one optional embodiment, the organic boron source includes at least one of triethyl borate, triisopropyl borate, and tributyl borate. In one optional embodiment, the alcohol solvent includes at least one of ethanol, isopropanol, and n-propanol.
[0012] In one optional embodiment, the organic pore expander is a mesoporous organic pore expander; Optionally, the mesoporous organic pore expander includes at least one of polyethylene glycol, polypropylene glycol, polyvinyl alcohol, and PEO-PPO-PEO triblock copolymer; In one optional embodiment, the inorganic pore expander is a gas-generating macroporous pore expander; Optionally, the gas-generating macroporous expanding agent includes an ammonium salt; Further optionally, the ammonium salt includes at least one of ammonium bicarbonate, ammonium carbonate, ammonium oxalate, and urea; Optionally, the adhesive includes at least one of water and CMC solution; Further optionally, the CMC solution has a mass fraction of 0.5-2%; Further optionally, the solid-liquid mass ratio of the water to the mixture A, the hydrophobic molecular sieve, and the pore-expanding agent is 100:(34-47).
[0013] Optionally, the mesoporous organic pore expander includes at least one of polyethylene glycol, polypropylene glycol, polyvinyl alcohol, and PEO-PPO-PEO triblock copolymer; Further optionally, the PEO-PPO-PEO triblock copolymer includes at least one of Pluronic P123 and Pluronic F127; In one optional embodiment, the silica-to-alumina ratio of the hydrophobic molecular sieve is ≥80; Optionally, the hydrophobic molecular sieve includes at least one of ZSM-5 type hydrophobic molecular sieve, β type hydrophobic molecular sieve, or hydrophobic mordenite.
[0014] Secondly, the present invention also provides a dechlorinating agent prepared by the above preparation method.
[0015] Thirdly, the present invention also provides an application of a dechlorinating agent in the petrochemical industry.
[0016] The technical solution of this invention has the following advantages: 1. A method for preparing a dechlorinating agent provided by the present invention includes the following steps: S1, obtaining a mixture A by co-precipitation reaction of calcium source, aluminum source, iron source and rare earth oxide; S2, extruding and calcining the mixture A, hydrophobic molecular sieve and pore expander to obtain an intermediate; S3, mixing a dispersant stabilizer, a complexing base catalyst, an organosilicon source, an organoboron source and an alcohol solvent, slowly adding water, and aging in stages to obtain a borosilicate nanosol; wherein the molar ratio of the organosilicon source and the organoboron source is 1:(0.20-0.25); S4, impregnating the intermediate in the borosilicate nanosol and calcining to obtain the dechlorinating agent.
[0017] The dechlorinating agent preparation method provided by this invention involves extruding and calcining a composite of calcium, aluminum, and iron sources with hydrophobic molecular sieves and pore-expanding agents to create a multi-metal oxide framework with a gradient pore structure and acid-base synergistic active sites. This framework is then surface-modified with borosilicate nanosol, controlling the molar ratio of organosilicon to organoboron sources to be 1:(0.20-0.25). This forms a Si-OB crosslinked network rich in unsaturated coordination defects, significantly enhancing the chemical adsorption capacity for HCl and organochlorines. This results in a dechlorinating agent with high specific surface area, large pore volume, and hydrothermal stability at the pore structure level. Furthermore, the method further... The calcination process effectively alleviates sintering shrinkage stress and, combined with the cross-linking and filling effect of the sol on microcracks, significantly improves the mechanical strength of the particles. This enables them to withstand industrial bed pressure drop and airflow scouring while reducing pulverization loss. The aforementioned advantages of the pore structure, along with the active defect sites formed by borosilicate sol modification, ultimately enhance the chlorine penetration capacity. This makes the dechlorinating agent superior to traditional products in terms of dechlorination depth, adaptability to operating conditions, and long-term operational stability. Furthermore, the preparation process is mild and controllable, and all key indicators can be clearly characterized by standard testing methods in this field, providing a reliable guarantee for industrial-scale production and quality control.
[0018] The calcium source serves a dual function as both a calcium source and a precipitation medium, undergoing an in-situ co-precipitation reaction with the aluminum source and rare earth oxides. This allows the calcium-based active components and the modified components in the rare earth oxides to simultaneously nucleate and anchor in situ on the carrier surface, replacing the traditional physical mixing and loading process. This method significantly improves the dispersion uniformity of the active components, effectively inhibits the agglomeration and sintering of active components under high-temperature conditions, and greatly improves the utilization rate of active sites and high-temperature stability. The calcination process allows the borosilicate nanosol to form a high-strength inorganic rigid coating layer after calcination. This coating layer does not block pores or cover active sites, effectively preventing the erosion and damage of the carrier matrix by high-temperature water vapor and sulfur components, and significantly improving the high-temperature hydrothermal stability, mechanical strength, and sulfur poisoning resistance of the dechlorinating agent.
[0019] 2. In the preparation method provided by the present invention, in step S3, the amount of dispersant stabilizer added is 1.0%-1.5% based on the mass of alcohol solvent. The dispersant stabilizer at this amount is only used to adjust the particle size of the nanosol and its wettability to the intermediate, and can be completely decomposed in the subsequent calcination process without any organic component residue, so as not to damage the continuity of the borosilicate glass mesh.
[0020] 3. The dechlorinating agent prepared by the method provided by the present invention can withstand rapid temperature changes caused by device heating and load fluctuations. It does not crack, pulverize, or damage the pore structure under high temperature sudden change conditions. It can meet the rapid commissioning requirements of the device in the low temperature stage of start-up, and can also be adapted to the high temperature and stable operating conditions during full-load production. It can achieve the goal of not needing to switch dechlorinating agents throughout the entire cycle and wide temperature range of the device, simplifying the process flow and reducing operation and replacement costs. Detailed Implementation
[0021] The following embodiments are provided to better understand the present invention, but the following embodiments do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the scope of protection of the present invention.
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having” and any variations thereof in the text of this application are intended to cover non-exclusive inclusion.
[0023] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0024] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the specific range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers from a to b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed herein, and "0-5" is merely a shortened representation of these numerical combinations. Furthermore, when a parameter is described as an integer ≥ 2, it is equivalent to disclosing that the parameter can be, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0025] In the description of the embodiments of this application, the term "and / or" is merely a description of the relationship between related objects, indicating that there can be three relationships. For example, A and / or B can represent three situations: A exists alone, A and B exist simultaneously, and B exists alone.
[0026] In the description of the embodiments of this application, the term "at least one" refers to one or more (including two).
[0027] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0028] Unless otherwise specified, all experimental steps or conditions in the examples were performed according to conventional experimental procedures and conditions in the art. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0029] The ZSM-5 hydrophobic molecular sieve used is a commercially available product with a silicon-to-aluminum ratio of 80. The hydrophobic mordenite zeolite used was a commercially available product with a silica-alumina ratio of 100. The β-type hydrophobic molecular sieve used is a commercially available product with a silicon-to-aluminum ratio of 120.
[0030] Example 1 This embodiment provides a dechlorination agent, and the specific operation and parameter settings are as follows: S1, calcium source (calcium hydroxide) and water are placed in a high-temperature reactor at a mass ratio of 1:2, heated to 50°C, and aluminum source (boehmite), iron source (iron oxide), and rare earth oxide (cerium dioxide) are added with rapid stirring. The mixture is then heated to 80°C and stirred at a constant temperature for 30 minutes. After cooling, the mixture is filtered and dried at 80°C to obtain mixture A. The mass ratio of calcium source, aluminum source, iron source, and rare earth oxide is 1:1:0.1429:0.005. S2, after mixing mixture A, hydrophobic molecular sieve (ZSM-5 type hydrophobic molecular sieve), and pore expander (polyethylene glycol 400 and ammonium bicarbonate mixed at a mass ratio of 1:1.1 for 10 min) for 30 min, the mixture is extruded into strips using a 2% CMC aqueous solution; the strip sample is dried at 80℃ for 2 h, then calcined at 280℃ for 1.5 h, and then calcined at 480℃ for 3 h to obtain an intermediate; the mass ratio of mixture A, hydrophobic molecular sieve, and pore expander is 1:0.03:0.03; S3. Pour the alcohol solvent (ethanol) into a stirred reactor, then add polyethylene glycol 400 and triethanolamine sequentially. Stir at room temperature and speed for 15 minutes until homogeneous. While continuously stirring, slowly add tetraethyl orthosilicate and stir for 20 minutes, then slowly add triethyl borate and continue stirring for 25 minutes. Add deionized water in batches at a slow and uniform rate to the above mixture, with a total addition time of 40 minutes. Allow to mature at room temperature in a sealed environment for 2.5 hours, then heat to 30°C and mature in a sealed environment for 4 hours to obtain borosilicate nanosol. The molar ratio of the organosilicon source, organoboron source, complexed base catalyst, alcohol solvent, and water is 1:0.20:0.09:9.0:2.2. The amount of dispersant stabilizer added is 1.03% of the mass of the alcohol solvent. S4. The intermediate is immersed in borosilicate nanosol at room temperature (volume ratio 1:1) for 15 min. After immersion, it is rinsed twice with ethanol and then calcined at 480°C for 4 h to obtain the dechlorination agent.
[0031] Example 2 This embodiment provides a dechlorination agent, which differs from Embodiment 1 only in that: In step S1, the mass ratio of the calcium source, aluminum source, iron source, and rare earth oxide is 1:2:0.1:0.024; cerium dioxide in the rare earth oxide is replaced with an equal mass of lanthanum trioxide. In step S2, the mass ratio of the mixture A, hydrophobic molecular sieve, and pore expander is 1:0.06:0.05; the parameters for the segmented calcination are: drying the strip sample at 80℃ for 2 hours, calcining at 280℃ for 1.5 hours, and finally calcining at 480℃ for 3 hours. In step S3, the molar ratio of the organosilicon source, organoboron source, complexed base catalyst, alcohol solvent, and water is 1:0.25:0.16:11.0:2.8; the amount of dispersant stabilizer added is 1.5% based on the mass of the alcohol solvent; the parameters for the segmented ripening are: dropping time 40 min, room temperature sealed for 2.5 h, and constant temperature ripening at 30℃ for 4 h. In step S4, the impregnation time is 15 minutes; the calcination parameters are 480°C for 4 hours.
[0032] Example 3 This embodiment provides a dechlorination agent, which differs from Embodiment 1 only in that: In step S2, the strip sample is dried at 80℃ for 2 hours, calcined at 280℃ for 1.5 hours, and finally calcined at 480℃ for 3 hours to obtain the intermediate.
[0033] Example 4 This embodiment provides a dechlorination agent, which differs from Embodiment 1 only in that: In step S2, the strip sample is dried at 120℃ for 3 hours, calcined at 320℃ for 1.5 hours, and finally calcined at 550℃ for 4 hours to obtain the intermediate.
[0034] Example 5 This embodiment provides a dechlorination agent, which differs from Embodiment 1 only in that: In step S3, the food is aged at room temperature in a sealed environment for 2.5 hours, and then heated to 30°C and aged in a sealed environment for 6 hours.
[0035] Example 6 This embodiment provides a dechlorination agent, which differs from Embodiment 1 only in that: In step S3, the food is aged at room temperature in a sealed environment for 3.5 hours, and then heated to 35°C and aged in a sealed environment for 4 hours.
[0036] Example 7 This embodiment provides a dechlorination agent, which differs from Embodiment 1 only in that: In step S4, calcination is carried out at 480℃ for 3.5 hours.
[0037] Example 8 This embodiment provides a dechlorination agent, which differs from Embodiment 1 only in that: In step S4, calcination is carried out at 500℃ for 4.5 hours.
[0038] Example 9 This embodiment provides a dechlorination agent, and the specific operation and parameter settings are as follows: S1, calcium source (calcium hydroxide) and water are placed in a high-temperature reactor at a mass ratio of 1:2, heated to 50°C, and aluminum source (activated alumina powder), iron source (iron oxide), and rare earth oxide (yttrium trioxide) are added with rapid stirring. The mixture is then heated to 80°C, stirred at a constant temperature for 30 minutes, cooled, filtered, and dried at 80°C to obtain mixture A; the mass ratio of calcium source, aluminum source, iron source, and rare earth oxide is 1:2:0.1:0.024. S2, after mixing mixture A, hydrophobic molecular sieve (β-type hydrophobic molecular sieve), and pore-expanding agent (polyvinyl alcohol with a degree of polymerization of 500 and ammonium oxalate mixed at a mass ratio of 1:1 for 10 min) for 30 min, the mixture is extruded into strips using a 2% CMC aqueous solution; the strip sample is dried at 120℃ for 2 h, calcined at 320℃ for 1.5 h, and finally calcined at 480℃ for 4 h to obtain an intermediate; the mass ratio of mixture A, hydrophobic molecular sieve, and pore-expanding agent is 1:0.03:0.05; S3. Pour the alcohol solvent (n-propanol) into a stirred reactor, then add polyethylene glycol 400 and triethanolamine sequentially. Stir at room temperature and speed for 15 minutes until homogeneous. While continuously stirring, slowly add tetraethyl orthosilicate and stir for 20 minutes. Then slowly add tributyl borate and continue stirring for 25 minutes. Add deionized water in batches at a slow and uniform rate to the above mixture, with a total addition time of 40 minutes. Perform a hydrolysis reaction at room temperature in a sealed environment for 3.5 hours, then heat to 30°C and cure in a sealed environment for 6 hours to obtain borosilicate nanosol. The molar ratio of the organosilicon source, organoboron source, complexed base catalyst, alcohol solvent, and water is 1:0.20:0.16:9:2.8. The amount of dispersant stabilizer added is 1.0% of the mass of the alcohol solvent. S4. The intermediate is immersed in borosilicate nanosol at room temperature (volume ratio 1:2) for 20 min. After immersion, it is rinsed twice with ethanol and then calcined at 500°C for 3.5 h to obtain the dechlorination agent.
[0039] Example 10 This embodiment provides a dechlorination agent, and the specific operation and parameter settings are as follows: S1, calcium source (calcium oxide) and water are placed in a high-temperature reactor at a mass ratio of 1:3, heated to 50°C, and aluminum source (fast powder removal), iron source (ferric hydroxide), and rare earth oxide (lanthanum trioxide) are added with rapid stirring. The mixture is then heated to 80°C, stirred at a constant temperature for 30 minutes, cooled, filtered, and dried at 80°C to obtain mixture A; the mass ratio of calcium source, aluminum source, iron source, and rare earth oxide is 1:1:0.1429:0.005. S2, mixture A, hydrophobic molecular sieve (hydrophobic mordenite zeolite), and pore expander (polypropylene glycol 400 and ammonium carbonate mixed at a mass ratio of 1:1.2 for 10 min) are mixed for 30 min and then extruded into strips using a 2% CMC aqueous solution; the strip samples are dried at 80℃ for 3 h, calcined at 280℃ for 1.5 h, and finally calcined at 550℃ for 3 h to obtain an intermediate; the mass ratio of mixture A, hydrophobic molecular sieve, and pore expander is 1:0.06:0.03; S3. Pour the alcohol solvent (isopropanol) into a stirred reactor, then add polyethylene glycol 350 and diethanolamine sequentially. Stir at room temperature and speed for 15 minutes until homogeneous. While continuously stirring, slowly add butyl orthosilicate and stir for 20 minutes. Then, slowly add triisopropyl borate and continue stirring for 25 minutes. Add deionized water in batches at a slow and uniform rate to the mixture over 60 minutes. Allow to mature at room temperature in a sealed container for 2.5 hours, then heat to 35°C and mature in a sealed container for 4 hours to obtain borosilicate nanosol. The molar ratio of the organosilicon source, organoboron source, complexed base catalyst, alcohol solvent, and water is 1:0.25:0.09:11:2.2. The amount of dispersant stabilizer added is 1.5% based on the mass of the alcohol solvent. S4. The intermediate is immersed in borosilicate nanosol at room temperature (volume ratio 1:1) for 30 min. After immersion, it is rinsed twice with ethanol and then calcined at 480°C for 4.5 h to obtain the dechlorination agent.
[0040] Example 11 This embodiment provides a dechlorination agent, which differs from Embodiment 1 only in that: In step S2, polyethylene glycol 400 is replaced with an equal mass of ammonium bicarbonate.
[0041] Example 12 This embodiment provides a dechlorination agent, which differs from Embodiment 1 only in that: In step S2, ammonium bicarbonate is replaced with an equal mass of polyethylene glycol 400.
[0042] Comparative Example 1 This comparative example provides a dechlorination agent, which differs from Example 1 only in that it does not impregnate borosilicate nano-sol. The specific operation is as follows: S1, calcium source (calcium hydroxide) and water are placed in a high-temperature reactor at a mass ratio of 1:2, heated to 50°C, and aluminum source (boehmite), iron source (iron oxide), and rare earth oxide (cerium dioxide) are added with rapid stirring. The mixture is then heated to 80°C and stirred at a constant temperature for 30 minutes. After cooling, the mixture is filtered and dried at 80°C to obtain mixture A. The mass ratio of calcium source, aluminum source, iron source, and rare earth oxide is 1:1:0.1429:0.005. S2, polyethylene glycol 400 and ammonium bicarbonate are compounded and mixed for 10 min to obtain a pore-expanding agent; mixture A, hydrophobic molecular sieve (ZSM-5 type hydrophobic molecular sieve) and pore-expanding agent are mixed for 30 min and then extruded into strips using a 2% CMC aqueous solution; the strip sample is dried at 80℃ for 2 h, calcined at 280℃ for 1.5 h, and finally calcined at 480℃ for 3 h to obtain a dechlorinating agent; the mass ratio of mixture A, hydrophobic molecular sieve and pore-expanding agent is 1:0.03:0.03.
[0043] Comparative Example 2 This comparative example provides a dechlorination agent, which differs from Example 1 only in that segmented calcination is not performed in step S2. The specific operation is as follows: In step S2, the strip sample is dried at 120℃ for 2 hours and then directly heated to 550℃ for 3 hours to obtain the intermediate.
[0044] Comparative Example 3 This comparative example provides a dechlorination agent, which differs from Example 1 only in that the molar ratio of tetraethyl orthosilicate to triethyl borate in the borosilicate nanosol prepared in step S3 is 2:1.
[0045] Comparative Example 4 This comparative example provides a dechlorination agent, which differs from Example 1 only in that segmented ripening is not performed in step S3. The specific operation is as follows: In step S3, after adding deionized water, the temperature is directly raised to 30℃ and kept constant for 6 hours.
[0046] Comparative Example 5 This comparative example provides a dechlorination agent, which differs from Example 1 only in that: In step S2, the high-silicon ZSM-5 hydrophobic molecular sieve is replaced with an equal mass of γ-crystalline alumina slag.
[0047] Experimental Example 1 (1) The specific surface area, pore volume and pore size of the dechlorinating agents prepared in each example and comparative example were detected by a physical adsorption instrument (model ASAP2460, Mack Instruments, USA).
[0048] (2) The dechlorination agents prepared in each example and comparative example were tested for particle strength in accordance with GB / T 44750-2024 "Measurement of particle compressive strength".
[0049] (3) The dechlorination agents prepared in each example and comparative example were tested to determine their dechlorination performance: The dechlorination agent sample was crushed and sieved to 20-40 mesh. 4 mL of the sample was weighed (M1) and placed into a reaction tube with an inner diameter of 10 mm. The temperature was raised to 350±5℃ and kept constant. Nitrogen gas was introduced (space velocity approximately 2000 h⁻¹).-1 () is used as a carrier gas, allowing it to pass through a concentration of 10000 mg / m³. 3 The hydrochloric acid solution carries away hydrogen chloride, adjusting the HCl concentration in the feed gas to 5000 mg / m³. 3 The evaluation was conducted under normal pressure. When a white precipitate appeared in the silver nitrate solution at the outlet of the reaction tube, the test was stopped immediately. The sample was taken out and weighed (M2). After grinding the sample after the reaction, about 0.2 g was weighed, dissolved in about 1.5 mL of dilute nitric acid and 150 mL of water, and the chlorine content was determined by potentiometric titration (X1). The dechlorination performance test was then completed.
[0050] Calculate the breakthrough chlorine capacity X2 of the dechlorinating agent using the following formula: ; Where M1 is the mass of the sample taken before the reaction, in g; M2 is the mass of the sample taken after the reaction, in grams; X1 represents the mass fraction of chlorine in the sample after the reaction, as measured by a potentiometric titrator.
[0051] The specific test results are shown in Table 1: Table 1 Test Results
[0052] The data above show that the dechlorinating agents prepared in each embodiment maintain high specific surface area, pore volume, and average pore size, while also achieving good mechanical strength and chlorine penetration capacity. In contrast, the comparative examples that did not use borosilicate nanosol impregnation, eliminated segmented calcination, changed the borosilicate sol ratio, omitted segmented ripening, or replaced the carrier or pore-expanding components showed deterioration in the pore structure of the material, resulting in a decrease in specific surface area and pore volume, ultimately leading to a significant reduction in chlorine penetration capacity. This indicates that the process steps and parameters of this application work synergistically to optimize the pore structure of the dechlorinating agent, effectively improving dechlorination adsorption performance while ensuring mechanical strength. Among them, although Comparative Example 1 has better specific surface area, pore volume, and average pore size, its particle strength is low. During the catalytic evaluation, it was observed that the sample underwent significant particle crushing, with a large amount of fine catalyst powder collected at the bottom of the sample tube. Particle breakage caused bed flow channel disturbance and loss of some active sites, leading to a significant decrease in its chlorine penetration capacity. This sample is difficult to adapt to actual working conditions.
[0053] Furthermore, the comparison shows that the dechlorinating agent prepared in Comparative Example 1 experienced a significant decrease in specific surface area after service, reflecting insufficient hydrothermal stability. The sample modified with borosilicate nanosol did not show a significant decrease in specific surface area after treatment under the same conditions, proving that the impregnation modification with borosilicate nanosol can effectively improve the hydrothermal stability of the material. In Comparative Example 4, due to the lack of segmented ripening, the organic boron and organic silicon sources were not sufficiently and gently hydrolyzed, resulting in the inability to uniformly condense Si-OB bonds and construct a uniform and stable borosilicate inorganic framework. This led to an abnormally high degree of densification in the sample, achieving high mechanical strength but significantly decreasing pore volume and specific surface area, and a markedly reduced chlorine penetration capacity. In Comparative Example 5, the alumina slag lacked the regular channels of molecular sieves and had a high impurity content, leading to a deteriorated pore structure. Although the strength was high, the chlorine penetration capacity was significantly reduced.
[0054] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for preparing a dechlorination agent, characterized in that, Includes the following steps: S1, calcium source, aluminum source, iron source and rare earth oxide are co-precipitated to obtain mixture A; S2, the mixture of material A, hydrophobic molecular sieve and pore expander is mixed, extruded into strips, and calcined in stages to obtain an intermediate; S3, a dispersion stabilizer, a complexing base catalyst, an organosilicon source, an organoboron source, and an alcohol solvent are mixed, water is added dropwise, and the mixture is aged in stages to obtain borosilicate nanosol; The molar ratio of the organosilicon source to the organoboron source is 1:(0.20-0.25). S4, the intermediate is impregnated in borosilicate nanosol and calcined to obtain the dechlorination agent.
2. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of the calcium source, aluminum source, iron source, and rare earth oxide is 1:(1-2):(0.1-0.1429):(0.005-0.024). And / or, in step S2, the mass ratio of the mixture A, the hydrophobic molecular sieve, and the pore-expanding agent is 1:(0.03-0.06):(0.03-0.05); And / or, in step S2, the pore-expanding agent includes organic pore-expanding agents and inorganic pore-expanding agents; Optionally, the mass ratio of organic pore expander to inorganic pore expander in the pore expander is 1:1-1.2; And / or, in step S3, the molar ratio of the organosilicon source, organoboron source, complexed base catalyst, alcohol solvent, and water is 1:(0.20-0.25):(0.09-0.16):(9-11):(2.2-2.8). And / or, in step S3, the amount of dispersant stabilizer added is 1.0%-1.5% based on the mass of the alcohol solvent.
3. The preparation method according to claim 1 or 2, characterized in that, In step S1, the coprecipitation reaction includes mixing calcium source and water at a mass ratio of 1:(2.0-3.0) to form a calcium source suspension, heating to 45-55℃ and adding aluminum source, iron source and rare earth oxide, heating to 75-85℃ and stirring for 25-35 minutes, and then separating the solid and liquid to obtain mixture A.
4. The preparation method according to any one of claims 1-3, characterized in that, In step S2, the segmented calcination includes drying at 80-120℃ for 2-3 hours, calcining at 280-320℃ for 1.5 hours, and finally calcining at 480-550℃ for 3-4 hours.
5. The preparation method according to any one of claims 1-4, characterized in that, In step S3, the water dripping time is controlled to be 40-60 minutes; And / or, in step S3, the segmented ripening includes room temperature sealed ripening for 2.5-3.5 hours, and temperature rise to 30-35°C sealed ripening for 4-6 hours.
6. The preparation method according to any one of claims 1-5, characterized in that, In step S4, the impregnation includes impregnating the intermediate and borosilicate nanosol at a volume ratio of 1:(1-2) at room temperature for 20-30 minutes. And / or, in step S4, the calcination temperature is 480℃-500℃, and the holding time is 3.5-4.5h; And / or, in step S2, the mixing step further includes adding a binder; Optionally, the adhesive includes at least one of water and CMC solution.
7. The preparation method according to any one of claims 1-6, characterized in that, The rare earth oxides include at least one of cerium dioxide, lanthanum trioxide, and yttrium trioxide; And / or, the calcium source includes at least one of calcium hydroxide and calcium oxide; And / or, the aluminum source includes at least one of boehmite, fast-release powder, and activated alumina powder; And / or, the iron source includes at least one of iron oxide, iron oxide red, and iron hydroxide; And / or, the dispersion stabilizer includes at least one of polyethylene glycol 400 and polyethylene glycol 350; And / or, the complexed base catalyst includes at least one of triethanolamine and diethanolamine; And / or, the organosilicon source includes at least one of tetraethyl orthosilicate and tetrabutyl orthosilicate; And / or, the organic boron source includes at least one of triethyl borate, triisopropyl borate, and tributyl borate; And / or, the alcohol solvent includes at least one of ethanol, isopropanol, and n-propanol.
8. The preparation method according to any one of claims 2-7, characterized in that, The organic pore expander is a mesoporous organic pore expander; Optionally, the mesoporous organic pore expander includes at least one of polyethylene glycol, polypropylene glycol, polyvinyl alcohol, and PEO-PPO-PEO triblock copolymer; And / or, the inorganic pore expander is a gas-generating macroporous pore expander; Optionally, the gas-generating macroporous expanding agent includes an ammonium salt; And / or, the hydrophobic molecular sieve includes a molecular sieve with a silica-to-alumina ratio ≥80 or an all-silica molecular sieve; Optionally, the hydrophobic molecular sieve includes at least one of ZSM-5 type hydrophobic molecular sieve, β type hydrophobic molecular sieve, Silicalite-1 all-silica molecular sieve, and hydrophobic mordenite zeolite.
9. A dechlorinating agent prepared by the preparation method according to any one of claims 1-8.
10. The application of the dechlorination agent according to claim 9 in the petrochemical industry.